Carotenoids from the ripening bacterium Brevibacterium linens impart color to the rind of the French cheese, Fourme de Montbrison (PDO). Issue 1 (2nd January 2020) - Giuffrida, Daniele; Monnet, Christophe; Laurent, Florence; Cacciola, Francesco; Oteri, Marianna; Le Piver, Mélanie; Caro, Yanis; Donato, Paola; Mondello, Luigi; Roueyre, Daniel; Dufossé, Laurent
Abstract: Rind color of some high-value PDO cheeses is related to the presence of carotenoids, but little is known about the structure of the pigmented compounds and their origin. Our objective was to describe the carotenoids extracted from the rind of a French cheese, Fourme de Montbrison, and to compare them with the pigments produced by a bacterial strain used as an adjunct culture in the cheese ripening process. Eleven carotenoids were detected in the cheese rinds or in the biomass of Brevibacterium linens . Most of the carotenoids from the rinds belonged to the aryl (aromatic) carotenoid family, including hydroxylated and non-hydroxylated isorenieratene. Chlorobactene, a carotenoid rarely found in food products, was also detected. Agelaxanthin A was identified in the cheese rinds as well as in the B. linens biomass. Occurrence of this compound was previously described in only one scientific publication, where it was isolated from the sponge Agela schmidtii . Graphical Abstract: